The evaulation of MTHFR c677t, MTHFR a1298c, Pai-1, Factor II and Factor V polymorphism in patients with opened spinal dysraphism and their healthy mothers - Öztürk, Sait; Kaplan, Metin; Erol, Fatih Serhat; Çakin, Hakan; Kara, Murat (Gulhane Medical School, University of Health Sciences, 2016)
We aimed to investigate the impact of existing genetic risk factors on the development of neural tube defect in children by evaluating MTHFR c677t, MTHFR a1298c, PAI- 1, Factor II, and Factor V gene polymorphisms in patients with open spinal dysraphism and in their healthy mothers. The study sample comprised cases scheduled for surgery in our clinic due to open spinal dysraphism and their healthy mothers. Mothers with a history of recurrent abortion, consanguineous marriage, obesity and thrombophilia, as well as those with a history of carbamazepine usage were excluded from the study with their children. A blood sample of 2 cc was collected from each patient and from their healthy mothers who was used in the deoxyribonucleic acid (DNA) analysis. The differences in allel and genotype distributions between the patients and their healthy mothers were evaluated by the ?2 test. A total of 34 individuals, 17 pediatric patients (Group 1) and their 17 healthy mothers (Group 2), were included in this study. As MTHFR c677t polymorphism frequency was higher in the Group 2 (p=0,024), MTHFR a1298c polymorphism frequency was higher in the Group 1 (p > 0,05). PAI-1 polymorphism frequency was higher in the Group 1, whereas Factor II and Factor V polymorphism frequencies were similar in both groups. In this study, although the healthy mothers were of normal phenotype, having heterozygous or mutant MTHFR c677t and a1298c genotype increases the risk of having children with neural tube defect. In terms of genetic counseling, knowing the genotype and allel status of the mother prior to a planned pregnancy may decrease the risk of having children with neural tube defect. © Gülhane Tip Fakültesi 2016.
Açik spinal disrafizmli hastalarda ve sağlikli annelerinde MTHFR c677t, MTHFR a1298c, Pai-1, Faktör II ve faktör V polimorfizminin değerlendirilmesi
Keywords: Genetic risc; Healthy mother; MTHFR; Neural tube defect